Enhancing Fraction in Glioma and Its Relationship to the Tumoral Vascular Microenvironment: A Dynamic Contrast-Enhanced MR Imaging Study - Mills, S.J.; Soh, C.; O'Connor, J.P.B.; Rose, C.J.; Buonaccorsi, G.; Cheung, S.; Zhao, S.; Parker, G.J.M.; Jackson, A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: EnF is a newly described measure of proportional tumor enhancement derived from DCE-MR imaging. The aim of this study was to assess the relationship between EnF and the more established DCE-MR imaging parameters: Ktrans, ve, and vp. MATERIALS AND METHODS: Forty-two patients with 43 gliomas (16 grade II, 3 grade III, and 24 grade IV) were studied. Imaging included pre- and postcontrast T1-weighted sequences through the lesion and T1-weighted DCE-MR imaging. Parametric maps of EnF, Ktrans, ve, and vp were generated. Voxels were classified as enhancing if the IAUC was positive (EnFIAUC60>0). A threshold of IAUC > 2.5 mmol.s was used to generate EnFIAUC60>2.5. Both measures of EnF were compared with the DCE-MR imaging parameters (Ktrans, ve, and vp). RESULTS: In grade II gliomas, EnFIAUC60>0 and EnFIAUC60>2.5 correlated with vp (R2 = 0.6245, P < .0005; and R2 = 0.4727, P = .003) but not with Ktrans or ve. In grade IV tumors, both EnFIAUC60>0 and EnFIAUC60>2.5 correlated with Ktrans (R2 = 0.3501, P = .001; and R2 = 0.4699, P < .0005) and vp (R2 = 0.1564, P = .01; and R2 = 0.2429, P = .007), but not with ve. Multiple regression analysis showed Ktrans as the only independent correlate of both EnFIAUC60>0 and EnFIAUC60>2.5 for grade IV tumors. CONCLUSIONS: This study suggests that in grade II tumors, EnF reflects vp and varies due to changes in vascular density. In grade IV gliomas, EnF is affected by Ktrans with secondary associated changes in vp. AIFarterial input functionDCE-CTdynamic contrast-enhanced CTDCE-MRdynamic contrast-enhanced MR imagingEnFenhancing fractionEnFIAUC60>0unthresholded enhancing fractionEnFIAUC60>2.5thresholded enhancing fractionIAUCinitial area under the concentration curveIAUC60initial area under the concentration curve during the first 60 secondsKtranscontrast-transfer coefficientrCBVrelative cerebral blood volumeveextravascular extracellular space volume per unit volume of tissueVEGFvascular endothelial growth factorVOIvolume of interestvpblood plasma volume per unit volume of tissueWHOWorld Health Organization